2021
DOI: 10.1103/physrevlett.127.233601
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Noise Insensitive Chiral Photonic Interface for Waveguide Circuit QED

Abstract: A chiral photonic interface is a quantum system that has different probabilities for emitting photons to the left and right. An on-chip compatible chiral interface is attractive for both fundamental studies of lightmatter interactions and applications to quantum information processing. We propose such a chiral interface based on superconducting circuits, which has wide bandwidth, rich tunability, and high tolerance to fabrication variations. The proposed interface consists of a core that uses Cooper-pair boxes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…4(a)]. Additionally, the emitter is assumed to be of giant atom form [60][61][62][63][64][65][66][67][68][69], which couples to the waveguide at two points x ± of channel A (or B), as depicted in Fig. 4(b).…”
Section: Periodical Interference Behavior Modulated By Giant Emitter'...mentioning
confidence: 99%
See 1 more Smart Citation
“…4(a)]. Additionally, the emitter is assumed to be of giant atom form [60][61][62][63][64][65][66][67][68][69], which couples to the waveguide at two points x ± of channel A (or B), as depicted in Fig. 4(b).…”
Section: Periodical Interference Behavior Modulated By Giant Emitter'...mentioning
confidence: 99%
“…Due to spinmomentum locking, the emitter chirally dissipates almost all its energy into one direction of the waveguide. Second, the emitter is considered as giant atom form, and couples to the waveguide at multiple sites [60][61][62][63][64][65][66][67][68][69]. Given that emitters' frequency is below two degenerate minima points induced by the spin-orbit coupling, the bound states will be periodically modulated by giant atom's size due to quantum interference.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work unveils the behavior of giant atoms coupled to a non-Hermitian Hatano-Nelson (HN) mode due to the asymmetric inter-site tunneling rates [30]. Giant atoms with chiral quantum optics [25,29,[31][32][33][34][35][36] have opened new possibilities to realize chiral or nonreciprocal phenomena such as directed emission and chiral bound states [37,38]. The entanglement dynamics [39] and non-Markovian disentanglement dynamics [40] in double-giant-atom waveguide-QED systems were studied for separated, braided, and nested coupling configurations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the modulating signal in our proposal is the electromagnetic current bias (rather than acoustic waves), which can be tuned much faster and freely. Our proposal can be employed for demonstrating chiral quantum optics widely discussed in [76][77][78][79][80][81][82][83][84][85], and provide a novel method to realize nonreciprocal transport of microwave photons without using the bulky ferrite circulator [86,87]. Very recent studies with circuit-QED setups showed that chiral emission from qubit pairs (coupled to a common waveguide) can be realized via linear interference process [80][81][82][83].…”
Section: Introductionmentioning
confidence: 99%